KREATIVITAS SISWA MELALUI KARYA KOLASE DENGAN KERTAS ORIGAMI PADA PELAJARAN SENI BUDAYA - Latifah, Nushrotul Latifah; Aulia, Silvia Natasya; Wijayanto, Wasis (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This research was motivated by various students' problems in making collage works using origami paper. Problems that occur will affect the final result of the collage work that has been created. The aim of this research is to determine students' creativity in sticking techniques using origami paper. Fine arts have a very important role in basic education and can develop students' visual skills, imagination and creativity. This research method includes observation, interviews, document analysis and documentation. This type of research uses qualitative research. The subjects of this research were 20 class IV teachers and students. The results of research at SD N 5 Cendono showed that students had different creativity in cutting origami paper and students had difficulty sticking the paper neatly. Making collages can increase student creativity and students are given the freedom to be creative so that the results are maximized. Based on these results, it can be concluded that the use of origami paper can increase the creativity of class IV students in arts and culture lessons on collage material. Keywords: Collage, Creativity, Fine Arts